Long-Chain Fatty Acid Receptors Mediate Relaxation of the Porcine Lower Esophageal Sphincter - Tsai, Ching-Chung; Li, Yi-Chen; Chang, Li-Ching; Tey, Shu-Leei; Lin, Kai-Jen; Huang, Shih-Che (Frontiers in Physiology, 2019)
Long-chain fatty acids activate the free fatty acid receptor 1 (FFA1) and FFA4. In the gastrointestinal system, FFA1 and FFA4 have been found in the pancreas and intestine. Fatty food and decreased lower esophageal sphincter (LES) motility are associated with gastroesophageal reflux disease. The effect of long-chain fatty acids on the esophageal motility is unknown. The purpose of this study is to investigate the effects of long-chain fatty acids on the porcine LES motility ex vivo using isometric transducers. In endothelin 1-precontracted porcine LES strips, the FFA1 selective agonists, fasiglifam, TUG424 and GW9508, caused marked relaxations in a concentration-dependent manner. The relative efficacies to elicit relaxation were GW9508 > TUG424 > fasiglifam in both clasp and sling strips. In contrast, the FFA4 specific agonists, TUG891 and GSK137647, produced mild relaxations. In addition, the endogenous FFA1 agonist DHA caused a mild relaxation whereas GW1100, an FFA1 antagonist, inhibited GW9508 induced relaxation of the porcine LES clasp and sling muscle. Both real-time PCR and immunohistochemistry revealed that FFA1and FFA4 were expressed in the porcine LES. Real-time PCR analysis showed that the FFA4 expression was much lower than FFA1. Taken together, long-chain fatty acid receptor agonists elicit relaxation of the porcine LES. FFA1 might influence LES motility.